IBU HEBAT JAGO BAKING: PRODUKSI KUE LUMPUR PANDAN, STROBERY CHEESE CAKE DAN BENTO - Rika Soihah; Yayan Sugiarto; Tina Andriana Suhanda; Intan Media Ratna; Fajar Pramono; Aditya Fakhri Lanang Sumadijo (Bajang Institute, 2025)
The community service program “Ibu Hebat Jago Baking” was implemented to enhance the technical skills and entrepreneurial motivation of PKK mothers in Kelurahan Isola through training in producing Kue Lumpur Pandan, Strawberry Cheese Cake, and creative bento meals. This program was initiated to address several issues faced by the community, including limited baking skills, lack of product standardization, minimal innovation, and weak business management. The training was conducted using a participatory and practical approach consisting of demonstrations, hands-on practice, discussions, and evaluations. The results show a significant improvement in participants’ technical abilities, with an average increase of more than 30% in recipe knowledge, baking techniques, product creativity, and packaging skills. Motivation to start a home-based culinary business also increased substantially, with 72% of participants expressing interest in selling products after the training. Additionally, participant satisfaction exceeded 89%, indicating the relevance and effectiveness of the program. This community service initiative successfully empowered PKK mothers by equipping them with applicable culinary skills and fostering entrepreneurial spirit, thus creating opportunities to improve family income and strengthen the local creative economy